An Unusual presentation of Acute Coronary Syndrome - Kohli, S C; Parajuli, M; Maskey, A; Acharya, C P (Journal of Nepal Health Research Council, 2011)
Acute coronary syndrome in elderly can manifest with a variety of atypical presentation and may be associated with other comorbid conditions. We present an atypical presentation of ACS in an elderly left handed female presenting with sudden onset of slurred speech preceded by dizziness and vomiting. After through clinical examination and investigation she was managed as a case of non ST elevation myocardial infarction and ischaemic stroke. Â  Key words: acute coronary syndrome, atypicalpresentation, ischaemic stroke